Race, gender, and leadership : re-envisioning organizational leadership from the perspectives of African American women executives - Parker, Patricia Sue, 1958- (LEA's communication series., 2004)
"Race, Gender, and Leadership: Re-envisioning Organizational Leadership From the Perspectives of African American Women Executives provides insights into the ways in which race and gender structure key leadership processes in today's diverse and changing workplace: This volume is appropriate for scholars and for advanced students studying race, gender and leadership, leadership, women's studies, African American studies, organizational communication and culture, and cross-cultural communication. The work will also be of interest to practitioners, including diversity trainers, activists, and community leaders, seeking resources for teaching new leadership ideas."--Jacket